Better Ways of Using Learners’ First Language in EFL Classrooms - Gulchehra Kamolova; Yaroslav Golovko (Euro Asian Journal Publishing, 2024)
The use of first language in English-as-a-foreign-language (hereinafter referred to as EFL) classrooms is still a controversial topic. Some studies have opposed the use of the students’ native language (hereinafter referred to as L1) and have called for its abandonment in EFL classes. On the other hand, a wide variety of studies have underscored the facilitative role of L1 in EFL classes and considered it as a helpful tool for boosting English learning. This article aims to find out the perceptions of teachers and students about the use of their first language in their EFL classroom in the teaching and learning processes.
Keywords: Perceptions of teachers; students; L1